COMMENTS ON ENVIRONMENTAL EFFECTS IN THE ORIGIN OF ANGULAR MOMENTA IN GALAXIES - Panko, Elena; Pajowska, Paulina; Godlowski, Wlodzimierz; Flin, Piotr (Одеські астрономічні публікації, 2012)
We examine the orientations of galaxies in 43 rich Abell galaxy clusters belonging to superclusters and containing at least 100 members in the considered area as a function of supercluster multiplicity. It is found that the orientation of galaxies in the analyzed clusters is not random and the alignment decreases with supercluster richness, although the effect is statistically significant only for azimuthal angles. The dependence of galaxy alignment on cluster location inside or outside a supercluster and on supercluster multiplicity clearly shows the importance of environmental effects on the origin of galaxy angular momenta. The comparison with alignment of galaxies in a sample of rich Abell clusters not belonging to superclusters is made too.